URGENSI STILASI BUDAYA DALAM PENDIDIKAN ISLAM DI AMPEL DENTA ABAD XV - Rakai Hino Galeswangi (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2022)
This research contains about how islam spreads widely from Surabaya City. The spread of Islam has been done by learning way. The founding teacher built a hermitage as the facility to support the learning process. This research has purpose to analyze and interpret an invention at 15th century in East Java, more precisely in the region of Surabaya. The object of this research is The Hermitage of Ampel Denta with the influential figure named Mohammad Ali Rahmatullah or well known as Sunan Ampel. The method of this research is library research with historical study. The data collection was carried out with library study with secondary data review. This research uses structural analysis on written sources, especially sources in foreign language. The result of this analysis is finding the existence of stylization proofs which has been done by Sunan Ampel for doing dawah and learning process in The Hermitage of Ampel Denta. By finding this interpret, this research may be useful for the next researches, especially in Islamic Religion field, education, and history.